PROBLEMS OF VALUE ADDED TAX TAXATION OF DISTRIBUTION TRANSACTIONS OF SOFTWARE IN RUSSIA - S. Kravchuk (Вестник университета)
Amendments presented as a stimulating measure for software developers did not catch realities of Russian software business and raised a number of questions including expediency of amendments of such stimulation. This article analyses questions business face during its activity and with support of court cases and calculations argues for the need of changes.